Pengaruh Debt Covenant dan Political Cost Terhadap Konservatisme Akuntansi - Iskandar, Okto Reyhansyah; Sparta, Sparta (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2019)
This research aims to understand and analyzes the effect of debt covenant, bonus plan, and political cost against company’s accounting conservatism. Independent variable for which used in this research was debt covenant measured by the ratio of leverage, bonus plan measured by company share ownership by managers, and political cost measured by the size of the company.While the dependent variable measured by accounting conservatism. The sample selection is using purposive sampling method, in order to obtain 36 observations of manufacturing company which narrowed to subsector industrial consumer goods and consistently listed at Indonesia Stock Exchange during the period 2012-2015. This research uses secondary data from company financial statements obtained from the Indonesia Stock Exchange. Multiple linear regression technique is used in this research to achieve analytical results. The result showed that debt covenant have negative insignificant effects to accounting conservatism, bonus plan have negative and significant effects to accounting conservatism, and political cost it has positive effects and significantl to accounting conservatism.